Association between Vitamins and Minerals with Antioxidant Effects and Coronary Artery Calcification in Adults and Older Adults: A Systematic Review - Machado, Alisson D.; Andrade, Gustavo Rosa Gentil; Levy, Jéssica; Ferreira, Sara Silva; Marchioni, Dirce Maria (Current Pharmaceutical Design, 2019)
Background: Coronary Artery Calcification (CAC) is considered an important cardiovascular risk factor. There is evidence that CAC is associated with an increased risk of atherosclerosis, coronary events and cardiovascular mortality. Inflammation is one of the factors associated with CAC and despite the interest in antioxidant compounds that can prevent CAC, its association with antioxidants remains unclear. Objective: This study aimed to systematically review the association between vitamins and minerals with antioxidant effects and CAC in adults and older adults. Methods: We conducted a systematic review using PubMed for articles published until October 2018. We included studies conducted in subjects aged 18 years and older with no previous cardiovascular disease. Studies involving animal or in vitro experiments and the ones that did not use reference methods to assess the CAC, dietary intake or serum levels of vitamin or mineral were excluded. Results: The search yielded 390 articles. After removal of duplicates, articles not related to the review, review articles, editorials, hypothesis articles and application of the inclusion and exclusion criteria, 9 articles remained. The results of the studies included in this systematic review suggest that magnesium is inversely associated with CAC and results on the association between CAC and vitamin E have been conflicting. Conclusion: Additional prospective studies are needed to elucidate the role of these micronutrients on CAC.
Keywords: magnesium